Characterization of microscopic distribution of fluids during gas displacing water and water displacing gas - WANG Zhouhua; ZHANG Hongyu; ZHANG Juan; LIAO Haoqi; HUANG Shilin (Youqi dizhi yu caishoulu)
Gas-water relative permeability measurement is a common method to describe the flow process in gas reservoirs with water. However， the results of relative permeability measurements vary significantly between different test methods and types of cores. To deepen the understanding of the microscopic distribution characteristics of fluid and flow mechanism during the gas-water flow process， this paper took YB Gas Field in Sichuan Basin as the research object and used nuclear magnetic resonance （NMR） technology to quantitatively describe the microscopic distribution of the two phases before and after relative permeability test. The distribution results were explained based on the gas-water two-phase flow mechanism obtained by the previous researchers with the visualization model. The results showed that the displacement efficiencies of micron-scale （>1 μm） pores during the water displacing gas and gas displacing water are basically the same with the two test methods， but the displacement efficiency in submicron-scale （0.1–1 μm） and nanoscale （<0.1 μm） pores during water displacing gas is relatively higher. Moreover， the water in the submicron-scale and nanoscale pores is not mainly produced during the gas displacing water. For fractured and porous cores， the displacement efficiencies in micron-scale pores of fractured cores are relatively low， while the displacement efficiencies in submicron-scale and nanoscale pores are relatively high. The difference in the microscopic distribution of fluids with the two test methods is mainly caused by the different capillary forces inside the pores， while the difference between the two types of cores is primarily due to the difference in their main flow channels.